Zero Budget Natural Farming in India - From inception to institutionalization - Khadse, Ashlesha; Rosset, Peter [UNESP] (Universidade Federal do Paraná, 2021)
This paper delineates the growth of Zero Budget Natural Farming (ZBNF) in India. From its origins as a peasant-led social movement in the state of Karnataka, to becoming institutionalized in a state program in Andhra Pradesh, ZBNF is attaining scale and reaching more and more peasant families. We look at some of the key factors that have triggered ZBNFs growth, as well as highlight some of the challenges and contradictions that may arise in the institutionalization process.
Agricultura natural de presupuesto cero en India - Desde su inicio hasta su institucionalización
Keywords: Agroecology; Budget natural farming; KRRS; Scaling-up agroecology; Subhash Palekar; Zero